The Reality of Using Electronic Media in Teaching Students with Visual Impairment: A Field Study on a Sample of Teachers in Algerian Schools - djedid, soulef; makhloufi, zakaria (El Omda in Linguistics and Discourse Analysis, 2025)
The study aimed to reveal the reality of the use of electronic media in the teaching of visually impaired people in various Algerian schools, and this study was addressed through an electronic questionnaire distributed to 10 professors from different states, to identify their trends towards the experience of including theme in the educational process, as well as to identify the obstacles to their use. The results showed that the Algerian school is experiencing acceptable use of electronic media in teaching the visually impaired, but suffers from some of the obstacles and difficulties that must be overcome in the future.